THE EFFECT OF INDIVIDUAL CHARACTERISTICS AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PERMODALAN NASIONAL MADANI MEKAR CIMAHI BRANCH - Fauzi, Fahrian Al; Wahyuningsih, Sri; Firdaus, Ahmad (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This study uses a quantitative approach, descriptive and associative. In this study, the author narrows the population, namely the number of employees of PNM Mekar Cimahi Branch 100 employees. The results of this study indicate that: 1) There is an influence of individual characteristics on employee work performance, as evidenced by the t-test value for the Individual Characteristics variable (X1) of 9,773 while the t-table value for N = 100 is 1,983. So 9.773 > 1.983, then H0 is rejected and Ha is accepted, it can be stated that Individual Characteristics (X1) have a significant effect on Employee Work Performance (Y). 2) There is an influence of the Work Environment on Employee Work Performance, proven by the t-count value for the Work Environment variable (X2) of 10.755, while the t-table value for N = 100 is 1.983. 3) There is an influence of Individual Characteristics and Work Environment simultaneously on Employee Work Performance, as proven by the results of the ANOVA test, the Fcount value is 390,320. While Ftable (a 0.05) for N = 100 is 2.70. So Fcount> from Ftable (a 0.05) or 390,320> 2.70 with a significant level of 0.000 because 0.000 <0.05, it can be said that Individual Characteristics (X1) and Work Environment (X2) simultaneously have a positive effect on Employee Work Performance (Y). The Adjusted R Square (R2) value is 0.889. This shows that 88.9% of Individual Characteristics (X1) and Work Environment (X2) simultaneously have an effect on Employee Work Performance (Y) while the remaining 11.1% is influenced by other factors not examined in this study.